Representações da História das mulheres no Brasil em livros didáticos de História - Ferreira, Angela Ribeiro (2005)
The main subject of the research is about the didactic mediation of lhe daily and academic knowledge, in relation to Women History, at the rnaking and utilization of the didactic books. It tries to answer how, if and how much of women social demands for equal representation and lhe possibilities resulted from academic research about the subject are found in History didactic books of 5" to 8" degree of the elementary school. In the last decade, the production about Women History in Srazil was large, but the new historical research perspective, with new objecls and approach considering forgotten agents, is slowly included in didactic production. In most of didactic books, great part of the texts still emphasizes political and economic aspects; although there is recognition of how important is the historiographic debate about women, this usually comes in complementary texts, separated from the main text. Based on historical knowledge about women and social representations theory, the analysis of the didactic History books shuws that new historiographic debates are put aside in the books content choice process. In order to fom the historical conscience, main History teaching objective, women must see themselves as subject in History. This work aríses the discussion of these elements, face to its urgent consideratian need to form personal and political identities suitable to the current stage of practices and social and juridical recognition of the women rights.